Studi Literatur Efektivitas Penggunaan Berbagai Jenis Pengencer yang Ditambahkan Antioksidan Terhadap Kualitas Semen Kambing (Capra aegagrus hircus) - Zaki A. A. Mubaraq; Nancy D. F. K. Foeh; Cynthia D. Gaina (Jurnal Veteriner Nusantara, 2023)
Goats are ruminants that have considerable potential. The livestock population data in the province of East Nusa Tenggara (NTT) has continued to increase from 2004 to 2018. The Artificial Insemination (AI) program has a function to improve genetic quality and livestock production. Extender is a mixture of various materials that can maintain the quality of spermatozoa in animal semen. Antioxidants to prevent the emergence of oxidant compounds in excess. The purpose of this literature study was to determine which semen extender has effectiveness in improving the quality of goat semen and the active substance that acts as an antioxidant as one of the substances that can improve the quality of the extender. The process of this literature study is carried out by searching and collecting various kinds of existing literature using Google Scholar, Google Patent, Pubmed then all existing references are compiled with the Mendeley application. Reference sources obtained are scientific journals, scientific articles/publications, e-books and national and international seminar proceedings by searching for "keywords" the effectiveness of using various types of extenders added with antioxidants on the quality of goat semen collected with a total of approximately 85 references. The results obtained from the literature study carried out are on the effectiveness of the semen extender, namely the more effective commercial extender, namely Andromed®, then the natural extender, namely guava leaves, while the compound extender is TGC+CLC (tris citrate glucose + Cholesterol Loaded). Cyclodextrin). Antioxidant active substances, both commercial and natural, that can increase the quality of goat semen, namely commercial antioxidants are Glutathione + 6 mM, while natural antioxidants are TKT (Egg Yolk Tris) + 4% Carrot Extract. The temperature and storage time of goat semen, the optimal temperature used for the equilibration time temperature is 5℃, at the cryopreservation temperature at -196℃, then at the optimal storage